مصطلحات علوم النبات في القرن الثامن الهجــــــري - معجم القاموس المحيط أنموذجا - عون, أسماء سالم محمد (مجلة الاصالة, 2025)
مصطلحات علوم النبات في القرن الثامن الهجــــــري - معجم القاموس المحيط أنموذجا